Inappropriate Use of Proton Pump Inhibitor Among Elderly Patients in British Columbia: What are the Long-term Adverse Events? - Ben-Eltriki, Mohamed; Chhabra, Manik; Cassels, Alan; Wright, James M. (Current Drug Safety, 2024)
Background: Proton pump inhibitors (PPIs) are one of the most used classes of drugs. For most indications, PPIs are only recommended up to 8 weeks duration. However, PPI use continues to expand. Regular and prolonged use of PPIs should be avoided because of the risk of adverse events.Objectives: The main objective of this study was to (1) investigate the extent of PPI usage in people aged 65 or older in the province of British Columbia (BC), Canada, (2) provide an overview of the harms associated with the long-term use of PPIs.Methods: We examined utilization trends of the PPIs in BC since the year 2009 using PharmaNet, BC's medication dispensing database where the information is accessible to community pharmacists. We performed a comprehensive literature search for relevant reviews reporting harms associated with long-term use of PPIs. A search was conducted from January 2014 to June 2022.Results: Between 2000 and 2018 BC's population grew by 20%, but the use of PPIs escalated to 257%. Of these older British Columbians, 62% had a cumulative exposure exceeding 2 years and 42% exceeded 5 years. This is alarming because the recommended treatment duration is 4-12 weeks for common indications including reflux esophagitis, and duodenal and gastric ulcers. Only 13.5% were dispensed PPIs for 90 days or less. Patients on long-term PPI therapy should be reassessed. Adverse events of PPI use are common among older adults. We identified over 217 systematic reviews published during the last 8 years of specific harms associated with long-term daily usage of PPIs. These harms include increased risks of death, cardiovascular disease, acute renal injury, chronic kidney disease, dementia, fractures, hypomagnesemia, iron deficiency, vitamin B12 deficiency, enteric infection (including C. difficile), pneumonia, and neoplasia (gastric cancer, carcinoids, and colon cancer), and drug interactions.Conclusion: This study revealed a high prevalence of PPI use among elderly populations in BC, Canada. The overutilization of PPIs is often a result of failure to re-evaluate the need for continuation of therapy. Published studies identified signals of serious harm from long-term PPI exposure. Healthcare providers with patients can reverse the relentless expansion of long-term PPI exposure by discussing the expected benefits and potential harms.
Keywords: dementia